2000
DOI: 10.1097/00004728-200001000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Brenner Tumor of the Ovary: CT and MR Findings

Abstract: Extensive amorphous calcification in a solid mass or solid component in a multilocular cystic mass is a characteristic finding of Brenner tumor of the ovary on CT and MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 12 publications
3
65
2
2
Order By: Relevance
“…Athey and Siegel 3 identified 3 of 4 tumors prospectively on sonography; 8 (47%) of 17 tumors in our series were not seen on sonography retrospectively. 3 Moon et al 4 reported that 5 (63%) of 8 patients had either a predominantly solid or at least a partly solid appearance on CT, lower than our result of 78%. Calcifications have been reported in 50% of Brenner tumors on sonography 3 and 83% on CT 4 ; both of these modalities showed 56% prevalence of calcifications in our series.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Athey and Siegel 3 identified 3 of 4 tumors prospectively on sonography; 8 (47%) of 17 tumors in our series were not seen on sonography retrospectively. 3 Moon et al 4 reported that 5 (63%) of 8 patients had either a predominantly solid or at least a partly solid appearance on CT, lower than our result of 78%. Calcifications have been reported in 50% of Brenner tumors on sonography 3 and 83% on CT 4 ; both of these modalities showed 56% prevalence of calcifications in our series.…”
Section: Discussioncontrasting
confidence: 89%
“…3 Moon et al 4 reported that 5 (63%) of 8 patients had either a predominantly solid or at least a partly solid appearance on CT, lower than our result of 78%. Calcifications have been reported in 50% of Brenner tumors on sonography 3 and 83% on CT 4 ; both of these modalities showed 56% prevalence of calcifications in our series. Magnetic resonance imaging may also show Brenner tumors, given their not infrequent incidental appearance on pelvic imaging studies.…”
Section: Discussioncontrasting
confidence: 89%
“…4 Several authors have reported that imaging features of benign Brenner tumors include very low signal intensity of the solid component on T 2 -weighted images, which re‰ects denseˆbrous collagen tissues, and CTˆndings of extensive amorphous calciˆcation within the tumors. [5][6][7] There have been onlyˆve reports of MR imagingˆndings of borderline or malignant Brenner tumors. [6][7][8][9] All four reports demonstrated that the tumor exhibited a cystic tumor with papillary or polypoid solid component.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] There have been onlyˆve reports of MR imagingˆndings of borderline or malignant Brenner tumors. [6][7][8][9] All four reports demonstrated that the tumor exhibited a cystic tumor with papillary or polypoid solid component. Although Moon's group 6 described the signal of the solid component on T 2 -weighted images as hypointense, the other four authors reported it as medium to high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation